Implementation of Discrete Mathematics to Improve The Understanding of The Concept of Space Building Based On Desktop Java - Purba, Oktaviana Nirmala (Al'Adzkiya, 2023)
The introduction of mathematical space building media is often applied in learning module media such as books. In this case it is less effective because students are less able to absorb what is conveyed by the teacher because the media is still a two-dimensional image. With the existence of a desktop java-based application, objects in the introduction of building space can be made into 3-dimensional images. This means that it is possible that this technology can be used as a tool for a more innovative method of introducing the Mathematical Space Formulas, such as by highlighting a camera connected to a cellphone the user can see in three dimensions how the shape of the real space.